THE INFLUENCE OF SCHOOL PRINCIPAL LEADERSHIP AND TEACHER COMPETENCE ON STUDENT DISCIPLINE THROUGH SCHOOL CULTURE AS A MEDIATING VARIABLE - Andriani Sariwardani; Kaswati; Umalihayati (Cakrawala Pedagogik, 2025)
Discipline is a crucial character trait that significantly influences the development of students' social attitudes.This research is based on the current low level of student discipline, which can be seen from habits such as talking in class during lessons, arriving late, and other similar behavior. The aim of this study is to examine how a principal's leadership and teacher competence affect student discipline, with school culture acting as an intervening variable. This research employs a quantitative approach, utilizing survey meth ods to collect data. The population in this study were elementary school teachers in cluster 2 of Pontang sub-district. The sample in this study consisted of 30 teachers selected from several elementary schools in cluster 2, Pontang District, Serang Regency. Data was collected through questionnaires, designed based on indicators for each variable. This research was measured using a Likert scale with five levels of answers, ranging from strongly disagree to strongly agree. Subsequently, the acquired data underw ent analysis using path analysis techniques, facilitated by SPSS version 25 software. The research findings indicated a significant influence of both the principal's leadership and teacher competence on student discipline. Furthermore, school culture had a notable impact on student discipline. School culture serves as a mediating factor, connecting the influence of principal leadership and teacher competence with student discipline.